Sustainable ammonia synthesis via thermochemical reaction cycle - Heidlage, Michael Gregory (Kansas State University, 2018)
Since its inception, the Haber-Bosch (HB) process for ammonia (NH₃) synthesis has allowed for a significant increase in global food production as well as a simultaneous decrease in global hunger and malnutrition. The HB process is estimated to be responsible for the subsistence of 40% of the world population as approximately 85% of the over 182 metric tons of NH₃ produced in 2017 was used as fertilizer for crop production. The natural gas consumed (mostly to generate H₂) represents approximately 2% of the global energy budget, while the CO₂ produced is about 2.5% of all global fossil CO₂ emissions. Approximately 40% of food consumed is essentially natural gas transformed by the HB process into agricultural products. However global food production will need to double due to expected increase in world population to 9.6 billion by 2050 and rising demand for protein among developing nations. A novel thermochemical reaction cycle for sustainable NH₃ synthesis at atmospheric pressure is explored herein. Both thermochemical and kinetic rationales are discussed regarding choice of Mn as the cycled reactant. The energetic driving force for these reactions is conceptually derived from concentrated solar energy. Mn was reacted with N₂ forming Mn-nitride, corrosion of Mn-nitride with steam at 500 °C formed MnO and NH₃, and lastly MnO was reduced at 1150 °C in a 4 vol % CH₄ – 96 vol % N₂ stream to Mn-nitride closing the cycle. Optimum nitridation at 800 °C and 120 min produced a Mn₆N₂.₅₈-rich Mn-nitride mixture containing 8.7 ± 0.9 wt. % nitrogen. NH₃ yield was limited to 0.04 after 120 min during nitride corrosion but addition of a NaOH promotor improved NH₃ yield to 0.54. Mn₆N₂.₅₈ yield was 0.381 ± 0.083 after MnO reduction for 30 min with CO and H₂ but no CO₂ detected in the product. Mn-nitridation kinetics were investigated at temperatures between 600 and 900 °C for 10 and 44 μm reactant powder particle sizes. That equilibrium conversion decreased with increasing temperature was confirmed. Jander’s rate law, which assumes gaseous reactant diffusion through a solid product layer, described the experimental data reasonably well. The rate constants and initial rates were as much as an order of magnitude greater for the 10 μm Mn reactant particle size. Additionally the activation energy was found to be 44.1 kJ mol⁻¹ less for the 10 μm reactant particle size. Reducing the particle size had a small but positive effect on Mn-nitridation kinetics. Further reducing particle size will likely have a greater impact. A review of relevant classical thermodynamics is discussed with special attention paid to open systems. Confidence issues regarding over-reliance on x-ray diffraction are considered with options suggested for mitigation. Opportunities for future work are assessed.
Keywords: Ammonia nitridation reduction thermochemical cycle